Sex and gender differences in the use of oral anticoagulants for non-valvular atrial fibrillation: A population-based cohort study in primary health care in catalonia - Giner-Soriano, Maria; Prat-Vallverdú, Oriol; Ouchi, Dan; Vilaplana-Carnerero, Carles; Morros, Rosa (Frontiers in Pharmacology, 2023)
Objectives: To describe the sex and gender differences in the treatment initiation and in the socio-demographic and clinical characteristics of all patients initiating an oral anticoagulant (OAC), and the sex and gender differences in prescribed doses and adherence and persistence to the treatment of those receiving direct oral anticoagulants (DOAC). Material and methods: Cohort study including patients with non-valvular atrial fibrillation (NVAF) who initiated OAC in 2011-2020. Data proceed from SIDIAP, Information System for Research in Primary Care, in Catalonia, Spain. Results: 123,250 people initiated OAC, 46.9% women and 53.1% men. Women were older and the clinical characteristics differed between genders. Women had higher risk of stroke than men at baseline, were more frequently underdosed with DOAC and discontinued the DOAC less frequently than men. Conclusions: We described the dose adequacy of patients receiving DOAC, finding a high frequency of underdosing, and significantly higher in women in comparison with men. Adherence was generally high, only with higher levels in women for rivaroxaban. Persistence during the first year of treatment was also high in general, being significantly more persistent women than men in the case of dabigatran and edoxaban. Dose inadequacy, lack of adherence and of persistence can result in less effective and safe treatments. It is necessary to conduct studies analysing sex and gender differences in health and disease.